Komunikasi Islam dalam Penegakan Amar Ma’ruf Nahi Munkar - Batubara, Jihan Afri; Abdullah; Sikumbang, Ahmad Tamrin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Islamic communication is an interaction process based on Islamic values, aiming to create peace and salvation in this world and the hereafter. This principle was practiced by the prophets, especially Prophet Muhammad (peace be upon him), in conveying the message of Islam, including upholding amar ma’ruf nahi mungkar. As part of dakwah, amar ma’ruf nahi mungkar plays a significant role in building a just and prosperous society. In the context of Islamic communication, its implementation must adhere to Sharia principles such as Divinity, Humanity, Morality, and Moderation while considering societal conditions. However, challenges in the field reveal many unethical practices due to limited understanding, literacy, and experience. This often leads to negative impacts that outweigh the expected benefits. Therefore, this study highlights the importance of applying the principles of Islamic communication in upholding amar ma’ruf nahi mungkar to achieve optimal dakwah goals. This study employs a qualitative approach using literature review as the primary method, relying on written sources such as books, articles, and previous research to explore the concepts of Islamic communication in upholding amar ma’ruf nahi mungkar. The conclusion emphasizes that the application of Islamic communication can make a tangible contribution to creating a harmonious, tolerant, and just society.